2021
DOI: 10.1093/neuonc/noab238
|View full text |Cite
|
Sign up to set email alerts
|

Improving the noninvasive classification of glioma genetic subtype with deep learning and diffusion-weighted imaging

Abstract: Background Diagnostic classification of diffuse gliomas now requires an assessment of molecular features, often including IDH-mutation and 1p19q-codeletion status. Because genetic testing requires an invasive process, an alternative noninvasive approach is attractive, particularly if resection is not recommended. The goal of this study was to evaluate the effects of training strategy and incorporation of biologically relevant images on predicting genetic subtypes with deep learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Finally, the performance of deep learning algorithms was not evaluated and compared in our study. Deep learning algorithms have been widely used in glioma molecular subtype prediction (41)(42)(43)(44)(45). However, deep learning usually needs a huge amount of dataset, such as hundreds or thousands of cases, and the dataset is limited for our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the performance of deep learning algorithms was not evaluated and compared in our study. Deep learning algorithms have been widely used in glioma molecular subtype prediction (41)(42)(43)(44)(45). However, deep learning usually needs a huge amount of dataset, such as hundreds or thousands of cases, and the dataset is limited for our approach.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for the radiologist to distinguish glioma genotypes based on these radiographic features in clinical practice. Fortunately, leveraging the recent advances in machine learning approaches, such as deep learning (DL), SVM, decision tree, etc., IDH mutation status prediction from MRI can be operated accurately and objectively [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, DL approaches have received the most notable attention for the reason of their outstanding performance in the molecular biomarker prediction from high-dimensional numeric information or image signal intensities [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, DL approaches have received the most notable attention for the reason of their outstanding performance in the molecular biomarker prediction from high-dimensional numeric information or image signal intensities [ 18 , 19 , 20 ]. Besides IDH prediction [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], DL is also widely applied to 1p/19q [ 21 , 22 ], MGMT [ 23 , 24 ] prediction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, a number of studies demonstrated the great potential of MRI-based image analyses for the tumor decoding of gliomas [ 4 ]. Here, various approaches to image analysis for predicting the genetic profile of gliomas have emerged in recent years [ 5 , 6 , 7 ]. On the one hand, radiomics features can be extracted from segmentations and be used to train machine learning algorithms [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, Guta et al were able to show that features extracted using CNN lead to better predictions for the grading of cerebral gliomas than features extracted using Radiomics [ 5 ]. Third, various networks have been established for direct image analysis of cerebral gliomas utilizing a variety of deep learning networks [ 6 , 12 ]. All approaches come with their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%